Inside Front Cover: Theranostic applications of multifunctional carbon nanomaterials (View 2/2023). Issue 2 (24th April 2023) - Masoudi Asil, Shima; Guerrero, Erick Damian; Bugarini, Georgina; Cayme, Joshua; De Avila, Nydia; Garcia, Jaime; Hernandez, Adrian; Mecado, Julia; Madero, Yazeneth; Moncayo, Frida; Olmos, Rosario; Perches, David; et al.
Abstract : Carbon nanomaterials are potent multifunctional materials with diverse biomedical applications in theranostic techniques. They can be considered as safe and efficient tools for non‐invasive diagnostic techniques such as magnetic resonance imaging (MRI). Various functionalized CNMs exhibit a great capacity to improve cell targeting of anticancer drugs. These therapeutic carbon‐based materials bring new hope for advancing the diagnosis sector for a wide range of diseases such as brain disorders, cardiovascular diseases, and cancer in the near future.